2023
DOI: 10.1177/20503121221150957
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the level of Knowledge and self-reported Practice toward safety precautions among Factory Workers in East Gojjam Zone, Northwest Ethiopia

Abstract: Background: According to the International Labor Organization, occupational accidents and diseases kill millions of workers every year. Objective: To assess factors associated with the level of knowledge and self-reported practice toward safety precautions among factory workers in the East Gojjam Zone, Northwest Ethiopia, 2021. Methods: An institution-based, cross-sectional study was conducted on 420 randomly selected factory workers. Data were collected through face-to-face interviews using structured questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…19 A possible explanation might be that experienced workers are more knowledgeable about safety measures in the workplace, and having good knowledge is associated with high compliance with safety precautions. 25,26 The current findings revealed that safety compliance was related to working hours, with those who worked at night having good practices regarding workplace health and safety requirements. According to one study, night shift workers may be more cautious and comply with safety, since working at night can be more physically and psychologically demanding, and workers may be more aware of the significance of safety to avoid accidents or injuries connected with working outside of normal business hours.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…19 A possible explanation might be that experienced workers are more knowledgeable about safety measures in the workplace, and having good knowledge is associated with high compliance with safety precautions. 25,26 The current findings revealed that safety compliance was related to working hours, with those who worked at night having good practices regarding workplace health and safety requirements. According to one study, night shift workers may be more cautious and comply with safety, since working at night can be more physically and psychologically demanding, and workers may be more aware of the significance of safety to avoid accidents or injuries connected with working outside of normal business hours.…”
mentioning
confidence: 63%
“… 19 A possible explanation might be that experienced workers are more knowledgeable about safety measures in the workplace, and having good knowledge is associated with high compliance with safety precautions. 25 , 26 …”
Section: Discussionmentioning
confidence: 99%